Study on USV Cluster Formation Control and Cooperative Obstacle Avoidance - Yuan Hsiang Chen; Alex Paul (International Journal of Engineering Continuity, 2022)
With the deepening of research on unmanned vehicles, research on USV (Unmanned Surface Vehicle) has gradually become extensive. In order to cope with complex Marine operations, the study of USV cluster collaborative operations has been emphasized. Therefore, this paper explores USV cluster formation and collaborative obstacle avoidance. In this paper, a formation control method of USV cluster is proposed based on the leader-follower architecture and the consistency algorithm. To solve the problem of formation cooperative obstacle avoidance, the traditional APF (APF method) is improved to avoid falling into the local optimal, and the cluster cooperative obstacle avoidance method is proposed. Finally, the simulation results show that the USV cluster formation control and obstacle avoidance methods are effective.